The Role of Quality of Work Life on Employee Engagement with Work Environment as a Moderating Variable - Linda Mora; Lania Muharsih; Nuram Mubina; Nita Rohayati (Edutran, 2023)
Companies involved in the construction sector also frequently encounter issues related to human resources (HR). Construction companies are industries engaged in the provision of facilities and infrastructure for the benefit of the community, subject to local government regulations. Construction projects have unique characteristics because their outcomes are not repetitive, they are temporary in nature, involve work accidents, are dominated by physical activity, and involve multiple elements of activity and parties involved in the implementation process. This creates a vulnerability to various obstacles. The purpose of this study is to look into the impact of work-life quality on employee engagement among construction workers in Karawang, with the work environment acting as a moderating factor. This study's data gathering method included the use of instruments in the form of employee engagement, quality of work life, and work environment measures. The hypothesis in this study was tested using Moderated Regression Analysis. The results of the analysis suggest a considerable positive association between the quality of work life and employee engagement among Karawang construction workers, with a correlation coefficient of rxy = 0.761 and a significant value of p = <0.001 (p<0.05). The moderation analysis results show that there is no connection between work life quality and work environment. This implies that the work environment is unable to operate as a mediator between work-life quality and employee engagement.